Validation of Amphetamine and Methamphetamine Measurement Method by Gas Chromatography-Mass Spectrometry - Yudiana, Dewi; Hartono, Adi; Sonata MS3, Herix (International Journal of Advanced Multidisciplinary, 2023)
Drug abuse is still very common in Indonesia, including in West Sumatra, which will result in psychological changes in users. A reliable method is needed to be able to detect the presence of narcotics and their metabolites in human specimens. The purpose of the study was to validate the mass spectrophotometric gas chromatography method for the measurement of amphetamine and metamphetamine. The benefits of research to ensure that the analytical method is accurate, specific, reproducible and resistant to the range of analytes to be analysed. The research method is by measuring the sample with GCMS (gas chromatography mass spectrometry) and then conducting a linearity test, detection limit test, accuracy test and precision test. The matrix used is urine specimen, spike is done with amphetamine and methamphetamine standards. From the results of the validation of amphetamine and methamphetamine measurement methods obtained MDL (method detection limit) 3.10 µg/L, LoD (limit of detection) 2.962 µg/L and LoQ (limit of detection) 2.962 µg/L. of Quantification) 9.873 µg/L. In the measurement of methamphetamine MDL 7.072 µg/L, LoD 6.757 µg/L and LoQ 22.253 µg/L. Accuracy of amphetamine and methamphetamine measurement methods 101.9% and 95.2% and reproducibility of amphetamine and methamphetamine measurements 3.83% and 6.743%. Measuring range and linearity of measurement of amphetamine and methamphetamine 25.0 µg/L - 200 µg/L with r = 0.9972 and 0.9992. Based on these data, the amphetamine and methamphetamine measurement method with gas chromatography-mass spectrometry is sensitive to measure amphetamine and methamphetamine in urine and fulfils the required criteria.